Awareness-Raising Program of Anemia Using Comics and Social Media for Teenage Girls - Sihotang, Urbanus (Journal of Saintech Transfer, 2022)
Nutritional problems that teenagers often experience are malnutrition, overweight, obesity and anemia. Risk of anemia in teenage girls is higher than in boys because of the increased demand of iron during the menstruation period. However this also becomes problematic because girls often limit their food intake. Blood Boost Formula is often prescribed to prevent anemia in teenage girls. The purpose of this community dedication activity is to find out about the compliance with consuming Blood Boost Formula, anemia prevalence and knowledge improvement of the audience after the program. This community dedication activity used comics and social media such as WhatsApp group. The target of this activity is 47 teenage girls of SMK Budi Nasional Tebing Tinggi students. Measured parameters for evaluation are medication compliance with consuming Blood Boost Formula, the degrees of awareness in anemia using questionnaire and anemia prevalence through Hemoglobin test using digital test. The results are showing that 69% of the students are not complying with the medication. There are 34% anemia prevalences. The pretest score was 20 points at the lowest and 60 points at the highest. While the post-test score was 27 points at the lowest and 67 points at the highest. There is an increase of mean value between pretest and post-test by about 10 points.